Retail Investor' Cognitive Bias In Digital Investment Platforms: A Systematic Litrature Review - Achmad Daffa Ralfsamy; Yusnaini . (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2026)
The digital transformation in the financial ecosystem has democratized investment access, yet simultaneously exposed retail investors to psychological vulnerabilities systematically induced by the architecture of digital investment platforms. This systematic literature review aims to critically investigate the escalation of cognitive biases, such as herding behavior and the illusion of control, triggered by hyper-connectivity and information asymmetry in contemporary trading applications. Grounded in the heuristics and biases theory, this study argues that digital platforms do not merely act as neutral facilitators, but actively serve as catalysts that exploit the bounded rationality of their users through cognitive overload and the absence of essential reflective pauses. The analysis of contemporary literature firmly rejects the classical assumption that conventional financial literacy education is adequate to mitigate these behavioral anomalies, considering that decision-making deviations operate at an instinctive and subconscious level. As a strategic implication and theoretical novelty, this research urges the deconstruction of the investor protection paradigm towards a behavior-centric transformation of choice architecture. Technology developers and regulators are required to integrate proactive digital nudging mechanisms and process accountability to transform applications from mere drivers of transaction velocity into systemic cognitive shields that effectively protect the financial stability of retail investors.